Bitcoin adoption in South Africa, an end user perspective - Kimani, Njinu (Department of Information Systems, 2022)
The development of electronic money and virtual currencies has led to the growing presence of bitcoin and other blockchain based, decentralized cryptocurrencies). The most popular of these cryptocurrencies being Bitcoin, a globally traded cryptocurrency, evidence of which is prevalent in South Africa with the formation of Bitcoin exchanges such as Luno in 2012. The advancement of Bitcoin in South Africa presents a number of opportunities for a number of role players in the financial, technology, retail and service sectors. However successful, wide spread adoption may also be hampered by various actors such as governments, financial institutions, merchants and the behaviour of end users. The usage of Bitcoin in developing countries for especially for international remittances and transfers has shown significant benefits such as lower transaction fees. The already prevalent use of mobile money in developing countries may aid Bitcoin's adoption. Mobile banking functions such as sending international remittances could easily be replaced by using a Bitcoin wallet, which offers much lower transaction costs than traditional banking services, especially when doing low value. It is believed that Bitcoin adoption and internet banking share parallels in that both involve the adoption of an innovating technology and both are susceptible to the effects of social phenomena and personal bias. This study investigates the adoption of Bitcoin in South Africa, a developing African country, from an end user's perspective. Importance will be placed on identifying and assessing challenges that may inhibit the widespread adoption of Bitcoin amongst end users, as well as drivers that may promote Bitcoin's adoption in South Africa. A significant finding is that end users' adoption decisions towards Bitcoin were mainly driven by the users propensity to hoard bitcoin in order to make financial gains. In addition, result demonstrability was also shown to be a key driver influencing the end users adoption decision. A modified version of the innovation diffusion theory is suggested in the discussion based on the findings of this study.